(untitled) (Swiss Medical Weekly, 2017)
Tramadol is widely prescribed for treating acute and chronic forms of pain. It is a weak mu-receptor opioid agonist and also increases concentrations of serotonin and noradrenaline within the limbic system of the brain. The therapeutic range of tramadol is relatively wide. Compared with other opioid agonists, there is little risk for developing tolerance and for abuse. Recent models of depression emphasise the subjective experience of a depressive mood as being, in part, a psychologically painful state. It is well established that psychological stress due to social separation/loss, disruption or betrayal of pre-existent significant interpersonal bonds is mediated by the activation of the mammalian PANIC (separation-distress) system. It is also known that this kind of stress can be soothed very effectively by very low doses of endogenous or exogenous opioid receptor agonists. These observations raise the question of whether tramadol can be an effective and safe treatment option for some forms of anxiety and depression in which elements of social loss or betrayal are involved. In support of this possibility, two clinical cases are presented, and ideas for development of new approaches targeting the endogenous opioidergic system in clinical practice are discussed.